Seroprevalence characteristics of hepatitis E virus among blood donors infected with hepatitis B virus - YU Qin; XU Tingting; YANG Hao; ZHAO Lei (Zhongguo shuxue zazhi)
[Objective] To investigate the seroprevalence characteristics of hepatitis E virus (HEV) among blood donors with hepatitis B virus (HBV) infection, so as to provide data support for the monitoring, prevention and treatment of HEV. [Methods] From January to December 2022, 219 samples positive for hepatitis B surface antigen (HBsAg), 142 occult hepatitis B virus infection (OBI) samples (HBV group) and 873 samples tested negative (control group) were collected. 361 samples were further tested with viral load assay and serological testing for five serological markers (HBsAg, HBsAb, HBeAg, HBeAb and HBcAb), and the DNA load was measured using real time fluorescence quantitative PCR. Commercially available enzyme-linked immunosorbent assays (ELISA) were used for the detection of anti-HEV IgG, anti-HEV IgM and HEV antigen (Ag). The Chi-square test or Fisher's exact test was used to assess the differences in the reactivity rates of anti-HEV IgG and anti-HEV IgM among different blood donor populations and different variables. Multivariable logistic regression was used to examine potential risk factors associated with anti-HEV IgG seroprevalence. [Results] In the HBV group, HBsAg positive donors exhibited low expression of antigen. The HBV DNA load of OBI infected donors ranged from 1 to 131.43 IU/mL (median 11.24 IU/mL). The prevalence of anti-HEV IgG and IgM antibody in the HBV group were 34.63% and 1.11%, respectively. Among them, the prevalence of anti-HEV IgG and anti-HEV IgM in the HBV group was 34.63% and 0, respectively (P<0.05), while in the OBI donors, they were 41.55% and 2.82%, respectively. In the normal donors, the reactivity rates for anti-HEV IgG and anti-HEV IgM were 18.67% and 1.49%, respectively. Statistical analysis showed that there was a difference in the reactivity rate of anti-HEV IgG between the HBV-infected donors and the normal donors (34.63% vs 18.67%, P<0.05), but no difference in the reactivity rate of anti-HEV IgM (1.11% vs 1.49%, P>0.05). No HEV Ag was detected in either group of blood donors. Multivariate logistic regression analysis indicated that age was an independent risk factor for anti-HEV IgG reactivity in both groups of blood donors. [Conclusion] The reactivity rate of anti-HEV IgG among HBV-infected blood donors was significantly higher than that in the normal donors in Wuhan, with age being an independent risk factor. Therefore, for HBV-infected donors, it is essential to strengthen and prioritize the prevention and treatment of HEV to reduce the spread of HEV.